2015
DOI: 10.4238/2015.december.22.1
|View full text |Cite
|
Sign up to set email alerts
|

One missense mutation in exon 2 of the PAX5 gene in Iran

Abstract: ABSTRACT. The PAX5 gene, which encodes the B-cell specific activator protein, is one of the most important factors in determination of B-cell development. This gene is the main target of somatic mutations in acute B lymphoblastic leukemia (B-ALL). For example, point mutations, deletions, as well as other gene rearrangements may lead to several forms of B-cell malignancy. In this study, we obtained 50 blood samples from patients diagnosed with ALL, and screened for PAX5 mutations using sequencing in exons 1, 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…As described in other germline PAX5 pedigrees [6][7][8] , the existence of asymptomatic carriers and the absence of immunodeficiency before the onset of BCP-ALL suggest the requirement of additional genetic alterations leading to the development of leukemia. Subjects II.2 and II.3 had a normal karyotype at the BCP-ALL stage.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…As described in other germline PAX5 pedigrees [6][7][8] , the existence of asymptomatic carriers and the absence of immunodeficiency before the onset of BCP-ALL suggest the requirement of additional genetic alterations leading to the development of leukemia. Subjects II.2 and II.3 had a normal karyotype at the BCP-ALL stage.…”
mentioning
confidence: 59%
“…The onset of BCP-ALL in patients with PAX5 G183S germline mutations located in the octapeptide domain is very early with a median age of 2 years old and associated with a loss of the chromosome 9p leading to the simultaneous losses of the second PAX5 allele and CDKN2A 6,7 . In contrast, the germline R38H variant (this work and 8 ) is associated with an older age of onset (11 to 25 years old) and a normal karyotype (Supplemental Figure 5 and Supplemental Table 5).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…A germline PAX5 missense variant affecting the same hotspot, c.547G>C (p.Gly183Arg), has been reported in one family [ 9 ]. Two unrelated families were found to carry a germline c.113G>A (p.Arg38His) variant [ 7 , 8 ]. Functional studies showed that PAX5 p.Arg38His is also a hypomorphic variant resulting in incomplete B-cell differentiation and is sufficient to predispose to leukemia [ 8 ].…”
Section: To the Editormentioning
confidence: 99%
“…Karyotypic analysis indicates translocations are early events whereas deletion of a second allele appears to be a secondary later event. Germline point mutations that inhibit PAX5 function also increase the likelihood of B ALL and some are accompanied by somatic deletion of the other PAX5 allele or cooperating PAX5 mutations (112)(113)(114)(115). The discovery of frequent PAX5 deletion and translocations in human ALL was rapidly followed by a large number of studies using some form of Pax5 deletion or translocation in mice to model B ALL.…”
Section: Pax5 Driven Models Of B All; a Case Study Of Multimodal Screens Converging On Common Findingsmentioning
confidence: 99%